ORGANIZATIONAL ASPECT OF SYSTEMATIC RESEARCH AND ANALYSES OF HUMAN RESOURCES (HR) POTENTIAL IN THE NUCLEAR INDUSTRY - Nikolay I. Ishchenko (Открытое образование (Москва))
The article observes organizational aspects of systematic approach to HR development in the areas of scientific industries, which uses and explores socially dangerous technologies. Specific aspects of the nuclear industry as a large scientific and production area have been observed in the article. Major steps and results of systematic HR research have been formulated.